A convenient and practical synthesis of β-diketones bearing linear perfluorinated alkyl groups and a 2-thienyl moiety - Taydakov, Ilya V.; Kreshchenova, Yuliya M.; Dolotova, Ekaterina P. (Beilstein Journal of Organic Chemistry, 2018)
A versatile and robust synthetic protocol for the preparation of β-diketones bearing 2-thienyl and perfluorinated alkyl radicals of different length or a methyl group was developed. This protocol is suitable for the preparation of multigram quantities of diketones without cumbersome purification procedures. Moreover, the known method for purification of diketones via copper chelates was improved considerably.
Keywords: Claisen condensation; copper chelate; β-diketones; perfluorinated esters; thiophene